Bisphenol A exposure during early pregnancy impairs uterine spiral artery remodeling and provokes intrauterine growth restriction in mice - Müller, Judith Elisabeth (2018)
Endocrine disrupting chemicals are long suspected to impair reproductive health. Bisphenol A (BPA) has estrogenic activity and therefore the capacity of interfering with endocrine pathways. No studies dissected its short-term effects on pregnancy and possible underlying mechanisms. Here, we studied how BPA exposure around implantation affects pregnancy, particularly concentrating on placentation and uterine remodeling. We exposed pregnant female mice to 50 μg/kg BPA/day or 0.1% ethanol by oral gavage from day 1 to 7 of gestation. High frequency ultrasound was employed to document the presence and size of implantations, placentas and fetuses throughout pregnancy. Blood velocity in the arteria uterina was analyzed by Doppler measurements. The progeny of mothers exposed to BPA was growth-restricted compared to the controls; this was evident in vivo as early as at day 12 as analyzed by ultrasound and confirmed by diminished fetal and placenta weights observed after sacrificing the animals at day 14 of gestation. The remodeling of uterine spiral arteries (SAs) was considerably impaired. We show that short-term exposure to a so-called "safe" BPA dose around implantation has severe consequences. The intrauterine growth restriction observed in more than half of the fetuses from BPA-treated mothers may owe to the direct negative effect of BPA on the remodeling of uterine SAs that limits the blood supply to the fetus. Our work reveals unsuspected short-term effects of BPA on pregnancy and urges to more studies dissecting the mechanisms behind the negative actions of BPA during early pregnancy.